1991
DOI: 10.3171/jns.1991.74.5.0845
|View full text |Cite
|
Sign up to set email alerts
|

A frameless, armless navigational system for computer-assisted neurosurgery

Abstract: A computer-assisted neurosurgical navigational system has been developed which displays intraoperative manipulation on the preoperative computerized tomography (CT) scans or magnetic resonance (MR) images. The system consists of a three-dimensional digitizer, a personal computer, and an image-processing unit. Utilizing recently developed magnetic field modulation technology, the three-dimensional digitizer determines the spatial position and orientation angles of the resin probe, triangle-shaped pointer, or su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(82 citation statements)
references
References 8 publications
3
74
0
5
Order By: Relevance
“…7,15,19,23) Electromagnetic navigation systems were created in 1991, with a computer-assisted neurosurgical navigational system using a magnetic source and sensor. 12) Since then, many in vivo and in vitro uses have been reported, and registration error as calculated by the various systems currently varies between 0.7 mm and 4.4 mm, showing no difference in accuracy compared with current optical navigation systems. 3,20) The results of our experiments showed that RMS error in all measurements was 1.2 mm and standard deviation was 0.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…7,15,19,23) Electromagnetic navigation systems were created in 1991, with a computer-assisted neurosurgical navigational system using a magnetic source and sensor. 12) Since then, many in vivo and in vitro uses have been reported, and registration error as calculated by the various systems currently varies between 0.7 mm and 4.4 mm, showing no difference in accuracy compared with current optical navigation systems. 3,20) The results of our experiments showed that RMS error in all measurements was 1.2 mm and standard deviation was 0.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, electromagnetic [54] and optical [56], [122] tracking systems, became commercially available in the early nineties. These systems usually provide sub millimeter tracking accuracy based on the detection of small navigation aids, referred to as sensors, fiducials, or markers.…”
Section: A History Of Image Guided Surgerymentioning
confidence: 99%
“…The different MR modalities that may be used for assessment include T 1 -and, T 2 -weighted images, MR angiograms, and functional MR imaging: all of these help to complete the initial diagnosis and aid planning of the surgical approach and subsequent patient management. The increased use of three-dimensional (3-D) image reconstruction methods [1,15,17,18,22,23,27] and surgical navigators [2,3,8,12,16,26,[30][31][32] has resulted in a substantial changes in the practice of neurosurgery. We have developed a protocol for the use of 3-D reconstructions that combines these modalities into one comprehensive model, which is then used for surgical planning and intraoperative navigation.…”
Section: Abstract * Low-grade Glioma * Three-dimensional Reconstructmentioning
confidence: 99%